Rekonstruksi Metodologi Fikih Kontemporer - Ansori Ansori (Al-Manahij: Jurnal Kajian Hukum Islam, 2018)
One of the causes of underdevelopment of Muslims is when fiqh is positioned equivalent to naá¹£á¹£ (Holy Scripture). When fiqh is equated with naá¹£á¹£, fiqh becomes sacred, there is no courage for people to criticize it, let alone make changes to existing fiqh provisions. As a product of reason (ijtihÄd), fiqh is not intended as a final legal provision. The ijtihÄd carried out by the generation after the death of the Prophet Muhammad must be made an important lesson for the need for the development of Islamic law (fiqh) to keep abreast of the times. Another important thing is that applying fiqh law must not only follow fiqh products, but also must understand the process. This means that knowing the methods used by jurists (fuqahÄâ€™) to process fiqh births should not be ruled out. Understanding the methods used by jurists (fuqahÄâ€™) will open the development of fiqh in the global era, so that fiqh products as a guideline for Muslims will remain relevant and responsive and able to solve contemporary problems.